Infaq vs. Bribery in Corruption Criminal Cases - Balkis, Fahira; Shafira, Maya; Jatmiko, Gunawan; Maroni, Maroni (Corruptio, 2024)
Infaq is an activity that is recommended for every Muslim. Giving Infaq can cause legal problems if the elements of the corruption crime are fulfilled. iAs happened in iCase Number i29/Pid.Sus-TPK/2022/PN iTjk. The Defendant was charged with article i5 paragraph I (1) of iLaw iNumber i20 of 2001 concerning the eradication of corruption, in conjunction with article i55(1) i1st iCriminal iCode, for giving in faq money amounting to IDR 250,000,000.00 to enroll his two nephews to the iFaculty iof iMedicine. iUniversity iof Lampung.An empirical juridical approach supports this research's informative juridical approach. The data are primary and secondary. Data collection is based on literature reviews and field studies. The data analysis method employed is qualitative analysis.